2009
DOI: 10.1002/cphc.200800811
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties of Mixed Lutetium/Yttrium Nitride Clusterfullerenes: Endohedral LuxY3−xN@C80(I) (x=0–3) Compounds

Abstract: The redox behavior of mixed lutetium/yttrium nitride clusterfullerenes of the series Lu(x)Y(3-x)N@C(80)(I(h), x = 0-3) is studied for the first time by means of cyclic voltammetry, fast-scan cyclic voltammetry, square-wave voltammetry, and electron paramagnetic resonance (EPR) spectroelectrochemistry. A reversible single-electron-transfer process, which does not result in an EPR signal, is detected during the anodic oxidation sweep of cyclic voltammetry experiments performed at different temperatures (296 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In the cathodic range, Lu 2 CeN@C 80 exhibits two electrochemically irreversible reduction steps with peak potentials (E pc ) at À1.43 and À1.92 V vs. Fc +/0 (corresponding peak potentials in square-wave voltammetry measurements are at À1.39 and À1.88 V). With slight variation of the peak potentials, this behavior is typical for all non-Sc M 3 N@C 80 NCFs studied to date, including Er 3 N@C 80 , Dy 3 N@C 80 , Tm 3 N@C 80 , Gd 3 N@C 80 , Nd 3 N@C 80 , Pr 3 N@C 80 and Lu x Y 3Àx N@C 80 , 3,4,[25][26][27]29,38 (for comparison, Fig. 7c shows cyclic voltammogram of Y 3 N@C 80 measured in the same conditions).…”
Section: Electrochemistry Of Lu 2 Cen@c 80mentioning
confidence: 77%
See 1 more Smart Citation
“…In the cathodic range, Lu 2 CeN@C 80 exhibits two electrochemically irreversible reduction steps with peak potentials (E pc ) at À1.43 and À1.92 V vs. Fc +/0 (corresponding peak potentials in square-wave voltammetry measurements are at À1.39 and À1.88 V). With slight variation of the peak potentials, this behavior is typical for all non-Sc M 3 N@C 80 NCFs studied to date, including Er 3 N@C 80 , Dy 3 N@C 80 , Tm 3 N@C 80 , Gd 3 N@C 80 , Nd 3 N@C 80 , Pr 3 N@C 80 and Lu x Y 3Àx N@C 80 , 3,4,[25][26][27]29,38 (for comparison, Fig. 7c shows cyclic voltammogram of Y 3 N@C 80 measured in the same conditions).…”
Section: Electrochemistry Of Lu 2 Cen@c 80mentioning
confidence: 77%
“…3,4,12,[21][22][23][24] In particular, the redox behaviour of NCFs has been studied in great detail, and it was found that the endohedral cluster is usually redox-inert, while the oxidation or reduction of NCFs occurs by changing the charge state of the carbon cage. 3,4,[25][26][27][28][29] Since the yield of NCFs in synthesis is much higher than that of the conventional metallofullerenes, it enhances the possibilities for research of the properties and applications of fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…152 The redox behaviour of mixed lutetium/yttrium nitride clusterfullerenes of the series LuxY 3Àx N@C 80 (x = 0-3) was studied for the first time by means of cyclic voltammetry and electron paramagnetic resonance. 153 Metallofullerene encapsulating the radioactive tracer Ac-225, Ac@C 82 was obtained and its electronic properties were studied by radiochromatography. 154 The structures of two newly synthesised endohedral fullerenes, Tm@C 94 and Ca@C 94 have been determined by single crystal X-ray diffraction.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…The redox behavior of M 3 N@C 80 fullerenes have been intensively studied in recent years and most of them show similar redox patterns with irreversible reduction processes. [4,[7][8][9][10] Only very recently Popov and coworkers reported that TiSc 2 N@I h -C 80 exhibits reversible reduction processes. [11] Although the cause of irreversibility remains unclear, tremendous progress has been made in this field.…”
mentioning
confidence: 98%
“…Moreover, the first reduction potential, compared to that of the parent Sc 3 N@I h -C 80 , is dramatically shifted from À1.26 V to À1.06 V, making it the most easily reduced M 3 N@I h -C 80 compound. [4,[8][9][10] It is notewor- À1.54…”
mentioning
confidence: 99%